Analisis Fenomena Perkembangan Bahasa Anak Usia Dini di Lingkungan Keluarga RA Perwanida 4 - Anna Sasa Sakinah; Amanda Ika Nurjanah; Lirya Dovelima Az-Zahra; Rahma Rahma; Ayu Wulandari; Nabila Septriani; Amanda Maharani (JURNAL PENDIDIKAN ROKANIA, 2026)
This research is a qualitative study using a library research approach that aims to analyze the phenomenon of early childhood language development in the family environment. Language development in early childhood is an important aspect because it supports children's communication, social interaction, and cognitive abilities. The family environment plays a major role as the first environment where children acquire language through interaction, communication patterns, and language stimulation provided by parents. Data collection techniques in this study were conducted through documentation by analyzing various scientific journals, books, and relevant articles related to early childhood language development and the influence of the family environment. The data analysis technique used the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The results of the study indicate that language development in early childhood is strongly influenced by the quality of interaction and communication within the family. Parents act as language models for children through daily conversations, storytelling activities, singing, and educational play. Supportive family environments, active communication, and proper language stimulation can improve children's vocabulary, speaking ability, and social interaction. On the other hand, limited verbal interaction, excessive gadget use, and less communicative environments can hinder children's language development. The study concludes that the family environment has a significant role in supporting the acquisition of first language in early childhood. Therefore, parents are expected to provide consistent language stimulation and create a communicative environment to optimize children's language development according to their developmental stages.